P102 The cambridge undergraduate simulation programme (CUSP): a one-year review. (31st December 2017) - Jafferji, D; Jackman, S; Judkins, N; Campbell, A
Abstract : Background: The value of simulation-based medical education (SBME) is becoming increasingly recognised as a valuable tool to improve confidence and competence of participants. 1 However, exposure of undergraduate students to this model of education is often impaired by factors that include the availability of physical resources, facilitator availability and the migratory nature of hospital placements. This programme was designed to address these issues by delivering SBME to senior medical students through the use of a student faculty. The programme was also designed to accommodate a pilot study investigating the impact of exposure to SBME on non-technical skill performance in senior medical students. Methodology: A programme was designed in conjunction with the student branch of the Association for Simulation Practice in Healthcare (sASPiH) around the key principles of a) patient and learner safety, b) robust and valuable SBME and c) professional development of a student faculty. Senior medical students were recruited and put through an initial training programme delivered by experienced facilitators. These medical students would form a student faculty and would be used to deliver clinical simulation opportunities to fellow senior medical students. Ongoing feedback and development opportunities were provided for the student faculty throughout the course of the year to enhance session delivery. Non-technical skill performance was designed to be assessed in participants through the use of video recorded pre-programme and post-programme simulated clinical scenarios. Performance in these scenarios was scored using an adapted version of the Anaesthetists' Non-Technical Skills (ANTS) behavioural marker system. 2 Outcome: A student faculty of 10 final year medical students were recruited and trained as SBME facilitators. Over the course of the programme 19 final and penultimate year medical student participants were exposed to 96 simulation sessions across six evening sessions. 20 medical students participated in pre-programme assessed simulated clinical scenario, 9 of which went on to attend a post-programme assessed simulated clinical scenario. Conclusions and Recommendations: Proof of concept has been demonstrated for the use of a student faculty to deliver a longitudinal SBME programme. Qualitative feedback demonstrated participants attached high educational value to this programme. A review of this programme will be used to modify the programme delivery so as to optimise participant benefit in subsequent iterations. Validation of the use of the ANTS behavioural marker system to assess non-technical skill performance in medical students has also occurred and will be used to develop a forthcoming quantitative research strand. References: . Ker J, Bradley P. Simulation in medical education. In: T. Swanwick, ed. Understanding Medical Education 2013. Chichester, West Sussex: John Wiley & Sons, pp. 175–192. . Fletcher G, Flin R, McGeorge P, Glavin R, Maran N, Patey R. Anaesthetists' Non-Technical Skills (ANTS): evaluation of a behavioural marker system. Br J Anaesth 2003;90(5):580–8.